Riedel's thyroiditis and retroperitoneal fibrosis in multifocal fibrosclerosis: positron emission tomographic findings. - Drieskens, O; Blockmans, D; Van den Bruel, A; Mortelmans, L (2002)
PURPOSE: The authors describe F-18 fluorodeoxyglucose positron emission tomographic (FDG PET) imaging features of Riedel's thyroiditis and retroperitoneal fibrosis in a patient with multifocal fibrosclerosis. MATERIALS AND METHODS: A 41-year-old woman in whom Riedel's thyroiditis had been diagnosed 7 months earlier was examined for fatigue, anorexia, and lower back pain, irradiating to the abdomen. Abdominal sonography and computed tomography showed a retroperitoneal mass. A biopsy of this mass showed histopathologic findings of retroperitoneal fibrosis. FDG PET was performed to evaluate the activity of the retroperitoneal fibrosis and to screen for other areas of fibrosclerosis. RESULTS: The FDG-PET images showed an intense hypermetabolic abdominal mass surrounding the aorta and increased glucose metabolism in the thyroid. No other sites of abnormal FDG metabolism were noted. These abnormalities disappeared after 4 months of steroid therapy. CONCLUSIONS: Sites of multifocal fibrosclerosis can be demonstrated by FDG PET, probably as a result of active inflammation involving lymphocytes, plasma cells, and fibroblast proliferation. FDG PET can help to establish the diagnosis of multifocal fibrosclerosis and evaluate the activity and patient response to corticosteroid therapy.